A phase feed-forward method to enhance inverter-grid system stability. (August 2023) - Liu, Junliang; Du, Xiong; Su, Xiaojie; Tai, Heng-Ming
Highlights: The limitation of the recent control methods (FCIN and FCOUT) are analyzed by analytical expressions. The proposed method greatly improves the system stability, since it overcomes the limitation that the recent control methods do not consider the duty cycle perturbations. The proposed method is simple and readily realized in the traditional control structure because it constructs an integrator and a high pass filter path outside the PLL. Abstract: The interaction between the inverter and the grid in weak grids may produce resonances that lead to reduced power quality and instability concern. The recently proposed control methods based on eliminating disturbances in the control loop avoid the challenging control parameter design faced by the existing stability-enhancing control methods. They are effective to overcome the instability concern, but may not be able to maintain stable operation of the system in certain situations. Moreover, they affect the steady-state output current of the system under the fluctuation of the grid. This paper proposes a phase feed-forward method in the dq-frame to overcome the problems encountered by these control methods, such as duty cycle perturbation and grid phase jump. The proposed method constructs an integrator and a high pass filter path outside the PLL. It is simple and readily realized in the traditional control structure. Simulation and experimental results are presented to demonstrate the effectiveness of the proposed control method.